"Everything is so relaxed and personal" – The construction of helpful relationships in individual placement and support. Issue 4 (1st October 2016) - Topor, Alain; Ljungberg, Amanda
ABSTRACT: The relationship with professionals is an important factor in relation to the outcome of interventions directed to persons with severe mental problems. However, the current knowledge regarding the development of helpful relationships within Individual Placement and Support (IPS) services is limited. The aim of the study was to investigate how participants in IPS services described their relationship with their IPS coach. The article is based on interviews from a Swedish government evaluation of IPS services, thematically analyzed. The results showed that the relationship with the coach is central for the participants' success in the service. The main theme, "something different - as a human being" highlighted that the conditions for the relationship are different within IPS as compared to traditional services. The other themes were "here and now action, " "closer to wish-fulfilment – impact on the self, " and "from role to person." The principles of IPS parallel the results from research about helpful relationships and offers good preconditions for the occurrence of such relationships. This can represent a bridge between evidence based methods and research on helpful relationships, and should be possible to implement in the development of evidence based methods as well as of treatment as usual.